2021
DOI: 10.3390/molecules26195951
|View full text |Cite
|
Sign up to set email alerts
|

Catechins: Therapeutic Perspectives in COVID-19-Associated Acute Kidney Injury

Abstract: Data obtained from several intensive care units around the world have provided substantial evidence of the strong association between impairment of the renal function and in-hospital deaths of critically ill COVID-19 patients, especially those with comorbidities and requiring renal replacement therapy (RRT). Acute kidney injury (AKI) is a common renal disorder of various etiologies characterized by a sudden and sustained decrease of renal function. Studies have shown that 5–46% of COVID-19 patients develop AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 142 publications
(272 reference statements)
1
9
0
Order By: Relevance
“…It effectively suppressed these viral replications in a dosedependent manner.A recent study by Bondonno et al [20] reported that it was found to have the inhibitory potential of SARS-CoV-2, specifically the main protease thereof. Similar catechins including gallocatechin-3-gallate, epigallocatechingallate and epicatechingallate are also claimed as active components in preventing SARs-CoV-2 Mpro; while, it has also been reported to have therapeutic potential in alleviating hyperinflammation in COVID-19 mediators due to its antiviral, antiseptic, antifibrotic and reduced oxidative stress synthesis and signaling [21,22]. According to the research reports of previous findings, we believe that these may potentially act concert with other catechins to inhibit viral replication and also act individually as an antiviral agent.…”
Section: Epicatechinmentioning
confidence: 99%
“…It effectively suppressed these viral replications in a dosedependent manner.A recent study by Bondonno et al [20] reported that it was found to have the inhibitory potential of SARS-CoV-2, specifically the main protease thereof. Similar catechins including gallocatechin-3-gallate, epigallocatechingallate and epicatechingallate are also claimed as active components in preventing SARs-CoV-2 Mpro; while, it has also been reported to have therapeutic potential in alleviating hyperinflammation in COVID-19 mediators due to its antiviral, antiseptic, antifibrotic and reduced oxidative stress synthesis and signaling [21,22]. According to the research reports of previous findings, we believe that these may potentially act concert with other catechins to inhibit viral replication and also act individually as an antiviral agent.…”
Section: Epicatechinmentioning
confidence: 99%
“…Recently, catechins ( 12 ) and their derivatives have attracted public attention because of their anti-tumor, antioxidative, and antimicrobial activities, in addition to easy availability, few toxic effects, and low cost [ 76 , 113 , 114 ]. Catechins have been shown to have nephroprotective activity and can prevent kidney damage caused by nephrotoxic drugs [ 115 , 116 ]. In future studies, the safety and efficacy of catechins in treating acute kidney injury should be further explored to provide reference values for clinical treatment.…”
Section: Other Effectsmentioning
confidence: 99%
“…The main signaling pathways involved are the activation of the Nrf2-HO-1 pathway and the inhibition of NF-κB by MAPK [6,26]. Studies in rats pretreated or treated with catechins showed significant protection or mitigation of the impairment of kidney function and glomerular and tubular lesions in models of AKI induced by glycerol, gentamicin, cisplatin, contrast, obstruction, ischemia/reperfusion, cardiopulmonary bypass, iron overload, cyclosporine, and tacrolimus [6,25,27,28]. Recent publications provided evidence that catechins can be used as antiviral and renoprotective agents in the prevention of COVID-19-induced AKI [27,29].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…The cell-surface receptor ACE2 is the binding site for the spike protein SARS-CoV-2 through the receptor binding domain of protein S (RBD) in the viral membrane, located in the S1 subunit of SARS-CoV-2, which recognizes ACE2 and forms the RBD-ACE2 complex, through which SARS-CoV-2 is activated for endocytosis, at which time its replication begins. In vitro, binding of EGCG to the spike protein of SARS-CoV-2 inhibits its interaction with ACE2 located on the host cell membrane and prevents endocytosis of SARS-CoV-2 [27]. Additionally, EGCG inhibits the initial replication of the virus by inhibiting M pro and RdRp [30].…”
Section: Diabetic Nephropathymentioning
confidence: 99%